2000
DOI: 10.1177/089686080002000509
|View full text |Cite
|
Sign up to set email alerts
|

Peritoneal Transport Characteristics, Comorbid Diseases and Survival in CAPD Patients

Abstract: Objective To evaluate the influence of initial peritoneal transport rate, serum albumin concentration, and comorbid diseases on continuous ambulatory peritoneal dialysis (CAPD) patient survival. Design A prospective single-center study with a long-term follow-up. Patients A total of 213 consecutive CAPD patients, who underwent a peritoneal equilibration test (PET) at a mean of 7 days (range 3 – 30 days) after beginning CAPD, were included in this study. One hundred twenty patients were male, 116 patients had c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
46
2
1

Year Published

2001
2001
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(54 citation statements)
references
References 33 publications
(42 reference statements)
5
46
2
1
Order By: Relevance
“…In 1998, the CANUSA study (42) and the Stoke PD Study (43) found that a fast transport status was associated with worse patient and technique survival independent of age, comorbidity, and residual renal function (RRF). This observation was subsequently confirmed by others (44,45). More recently, Heaf and Van Biesen, using the PDC test, suggested that patients with a high peritoneal transport status (which they found to be associated with peritoneal or systemic inflammation and large pore fluxes) exhibit poor prognosis (46,47).…”
Section: Pm Function and Clinical Outcomessupporting
confidence: 73%
“…In 1998, the CANUSA study (42) and the Stoke PD Study (43) found that a fast transport status was associated with worse patient and technique survival independent of age, comorbidity, and residual renal function (RRF). This observation was subsequently confirmed by others (44,45). More recently, Heaf and Van Biesen, using the PDC test, suggested that patients with a high peritoneal transport status (which they found to be associated with peritoneal or systemic inflammation and large pore fluxes) exhibit poor prognosis (46,47).…”
Section: Pm Function and Clinical Outcomessupporting
confidence: 73%
“…multivariate analysis. 9,16 A few studies have not found an association; however, in some cases this is likely to be due to being under powered, 17,18 or an association was found on univariate analysis only [19][20][21] or to be associated with morbidity but not mortality. 22 Two large studies have failed to find an association; in both cases, there were potential reasons for this, including a largely prevalent patient population, 23 nonstandard methods of measuring membrane function, and a non-prospective study design.…”
Section: Membrane Function and Clinical Outcomesmentioning
confidence: 99%
“…Several studies have looked at this and their findings are summarized in Table 1. 3,[6][7][8][9][10] Before discussing these in detail, two things should be noted. First, in general, although statistically significant relationships are found, they explain relatively little of the variance in solute transport.…”
Section: Variability In Membrane Functionmentioning
confidence: 99%
“…13 Higher protein loss in patients with higher MTS has been proposed to contribute to malnutrition or fluid overload, which may in turn predispose to peritonitis. [14][15][16] Although there is agreement that hypoalbuminaemia is an independent risk factor for peritonitis and technique failure, any relationship between MTS and peritonitis has not been properly examined. The largest study from Australia and New Zealand to date 8 did not account for peritonitis as a confounder, and other studies have reported contradictory results.…”
mentioning
confidence: 99%